Analysis of the Creation Intention of the Yuan Drama Sorrow in the Han Palace from the Tailoring of Zhaojun’s Story - Sheng Wu (Forest Chemicals Review)
The story of Wang Zhaojun’s going out of the frontier experienced the flow from historical legends, poetry, notes to folk raps. Ma Zhiyuan created the drama Sorrow in the Han Palace after careful artistic tailoring. It unfolds the plot under the situation of strong Hu and weak Han, creates a rich atmosphere of tragedy, extolls the patriotic spirit and national integrity of Zhaojun, effectively castigates the officials of the Han Dynasty who were greedy for life and afraid of death and bereaved and humiliated the country, and gives sympathy to the victims of Emperor Han Yuan. It embodies the pain of the decline of the author’s family and country as well as the perplexity and sad feeling of life arising from the loss of a good life in the troubled times.